HALAL CERTIFICATE POLICY: CORRELATION OF CAMPAIGN AND CREATING BRAND IMAGE ON CONSUMER INTEREST TO BUY WARDAH COSMETICS IN BANDUNG - Ine Aprianti; Taufik Zulfikar; Annisa Rachmawati; Lucy Nurfadilah (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2022)
The Halal certification policy has an effect on competition, including competition in the world of the cosmetic industry, a phenomenon marked by the level of competition between cosmetic companies that are getting tighter. To increase competitiveness and so that the brand is always at the top of the consumer's mind (top of mind), the company must always hold a campaign so that the creation of the brand image is always maintained and will eventually lead to buying interest. This study aims to analyze and prove the effect of halal certificate policies in campaigns and brand image creation on buying interest. The research method was used quantitatively with the number of respondents as many as 100 people to determine the sample by chance at a mall in Bandung. The data was obtained by giving closed questions to the respondents. The analytical tool used is Multiple Linear Regression. The results of the study indicate that the campaign and the creation of a Brand Image, either partially or jointly, have an effect on Buying Interest.